The Impact of Corporate Social Responsibility on M&A Premiums : Evidence from the European M&A Market - Naukkarinen, Olli-Matias (My University, 2025)
This thesis examines the relationship between corporate social responsibility (CSR) performance and M&A premiums in the European mergers and acquisitions (M&A) market, focusing on the perspective of target companies. It investigates whether the CSR performance of the target company influences the premiums paid by acquiring firms and whether different CSR dimensions, environmental and social, have distinct effects on valuation. The study also explores how the valuation of CSR differs between domestic and cross-border M&A transactions, addressing gaps in existing literature that mainly focus on the acquirer’s perspective or specific geographic regions. Using a dataset of 205 M&A transactions involving publicly traded target companies in the Eurozone between 2012 and 2024, this study employs a multivariate OLS regression model to analyze the impact of CSR performance on acquisition premiums. The CSR performance is measured through ESG scores, focusing on environmental and social factors, while controlling for firm-specific and deal-specific characteristics. The findings reveal that the target company’s CSR performance does not have a significant impact on the premium paid in M&A transactions, meaning that European target companies are not rewarded for their CSR investments when acquired. A similar result is observed even in higher-risk cross-border deals. These findings suggest that, in Europe, companies generally maintain a high level of CSR due to EU policies and regulations. As a result, a target company’s CSR performance does not significantly influence bid premiums.

Tämä tutkielma tarkastelee yritysvastuun (CSR) ja yritysostojen (M&A) preemioiden välistä suhdetta Euroopan markkina-alueella keskittyen ostettavan yrityksen näkökulmaan. Tutkielman päätavoitteena on selvittää, vaikuttaako kohdeyrityksen CSR-suorituskyky ostajan maksamaan preemioon. Lisäksi tutkimuksessa tarkastellaan erikseen ympäristö- ja sosiaalielementtien vaikutusta kohdeyrityksen arvostukseen sekä syvennytään tarkastelemaan eroja kotimaisten ja kansainvälisten yrityskauppojen välillä. Aikaisempi kirjallisuus on keskittynyt pääasiassa ostajan näkökulmaan tai tiettyihin maantieteellisiin alueisiin ja tämän tutkielman tarkoituksena on laajentaa kirjallisuutta keskittymällä ostettavan yrityksen näkökulmaan Euroopan markkina-alueella. Tutkimuksessa hyödynnetään aineistoa, joka koostuu 205 julkisesti noteeratun kohdeyrityksen yrityskaupasta Euroalueella vuosien 2012–2024 välillä. CSR-suorituskyvyn vaikutusta yritysostojen preemioihin analysoidaan käyttäen apuna monimuuttujaista OLS-regressiomallia. CSR-suorituskykyä mitataan hyödyntämällä ESG-ratingin ympäristö- ja sosiaalitekijöitä. Lisäksi regressiomallissa hyödynnetään useista yrityskohtaisia ja transaktiokohtaisia kontrolli muuttujia. Tulokset osoittavat, että kohdeyrityksen CSR-suorituskyvyllä ei ole merkittävää vaikutusta yrityskaupassa maksettuun preemioon, kun ostettava yritys on eurooppalainen. Tämä tarkoittaa sitä, että eurooppalaisia kohdeyrityksiä ei palkita CSR-investoinneista yrityskaupassa korkeammalla preemiolla. Sama tulos havaitaan myös korkeampiriskisissä kansainvälisissä yritysostoissa. Havainnot viittaavat siihen, että Euroopassa yritysten CSR-suorituskyky on yleisesti korkea EU:n säädösten vuoksi.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance